A preliminary assessment of crab predation on epifaunal fouling organisms attached to eelgrass at Martha's Vineyard, Massachusetts, USA - Carman, Mary R.; Grunden, David W. (Management of Biological Invasions, 2019)
© The Author(s), 2019. This article is distributed under the terms of the Creative Commons Attribution License. The definitive version was published in Carman, M. R., & Grunden, D. W. A preliminary assessment of crab predation on epifaunal fouling organisms attached to eelgrass at Martha's Vineyard, Massachusetts, USA. Management of Biological Invasions, 10(4), (2019): 626-640, doi:10.3391/mbi.2019.10.4.04. Eelgrass (Zostera marina) is an ecologically valuable seagrass which is exposed to a wide range of stressors and has declined worldwide. The proliferation of epifaunal fouling organisms such as the sponge Halichondria panicea, colonial tunicate Botryllus schlosseri, and solitary tunicate Molgula manhattensis represents additional stress for eelgrass. Predation of this epifauna that would otherwise cause harm to eelgrass, will likely reduce their impact. On Martha’s Vineyard, an island in the Northwest Atlantic off southern Massachusetts, USA, green crabs Carcinus maenas and spider crabs Libinia dubia were examined as potential predators of sponges and tunicates attached to eelgrass. Crabs were somewhat starved for one week and then, in the lab, put in enclosures with three eelgrass shoots and tunicate/sponge epifauna. Consumption of prey items and crab survival were measured at one and 24 hours. After one hour, C. meanas did not consume any prey, while predation by L. dubia did occur. After 24 hours, C. meanas had still not consumed any tunicates or sponges, while L. dubia consumed eelgrass with H. panicea (100%); B. schlosseri (40% completely, 40% partially, and 20% unconsumed); and M. manhattensis (60% completely, 20% partially, and 20% unconsumed). High densities of M. manhattensis often occurs on eelgrass at Martha’s Vineyard (up to 6,700 per m2), thus we sought to determine a M. manhattensis consumption rate for L. dubia in the lab. A single L. dubia can consume at least 30 M. manhattensis in a 24-hour period. Because of the recent declines in eelgrass acreage, understanding the ecological ...